THE YELLOW BOOK GALLERY IN MARTAPURA, BANJAR REGENCY - Ramadhan, Muhamad (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2023)
Martapura is called the city of Mecca because it is known as a religious city. In 2019, the Banjar Regency government plans to create a place that houses the Yellow Book which will be located in Murung Kenanga Village, Martapura. The Yellow Book is the source of classical Islamic readings. The place that housed this was later called The Yellow Book Gallery. The purpose of this design is to learn and inform the general public, also as a center for the study and development of the Yellow Book to preserve it. The design method used is the method of Islamic architecture with the principle of habluminallah, habluminannas and hambluminal'alam. The design concept is a communicative and educative concept which is the result of linking the ta'dib program concept (ilm’, ta'lim, and tarbiyah) with the method of Islamic architecture.